(2 x - 1)/3 = (x + 5)/8 - (1-x)/2=8(2x−1)=
3(x+5)−12(1−x)=
16x−8=3x+15−12+12x=
16x−8=15x+3=
16x−8−15x=
3x−8=3
x=3+8
x=11
Объяснение:
х=11
умножим обе части уравнения на 24 тогда имеем
8(2х-1)=3(х+5)-12(1-х)
16х-8=3х+15-12+12х
16х-8=15х+3
16х-15х=8+3
(2 x - 1)/3 = (x + 5)/8 - (1-x)/2=8(2x−1)=
3(x+5)−12(1−x)=
16x−8=3x+15−12+12x=
16x−8=15x+3=
16x−8−15x=
3x−8=3
x=3+8
x=11
Объяснение:
х=11
Объяснение:
умножим обе части уравнения на 24 тогда имеем
8(2х-1)=3(х+5)-12(1-х)
16х-8=3х+15-12+12х
16х-8=15х+3
16х-15х=8+3
х=11